2020
DOI: 10.1038/s41537-020-00111-6
|View full text |Cite
|
Sign up to set email alerts
|

Functional brain networks in the schizophrenia spectrum and bipolar disorder with psychosis

Abstract: Psychotic experiences have been proposed to lie on a spectrum, ranging from subclinical experiences to treatment-resistant schizophrenia. We aimed to characterize functional connectivity and brain network characteristics in relation to the schizophrenia spectrum and bipolar disorder with psychosis to disentangle neural correlates to psychosis. Additionally, we studied antipsychotic medication and lithium effects on network characteristics. We analyzed functional connectivity strength and network topology in 48… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 62 publications
(120 reference statements)
2
25
0
Order By: Relevance
“…The connection intensity of SCH patients was lower than that among BD patients and HCs, but there was no difference in network topology between groups. In contrast, BD patients in another study had a less complete network topology, while the connection intensity was not disturbed (78). Recent studies have found that the connectivity of the whole brain network was increased in SCH patients but not in BD patients.…”
Section: Discussionmentioning
confidence: 79%
“…The connection intensity of SCH patients was lower than that among BD patients and HCs, but there was no difference in network topology between groups. In contrast, BD patients in another study had a less complete network topology, while the connection intensity was not disturbed (78). Recent studies have found that the connectivity of the whole brain network was increased in SCH patients but not in BD patients.…”
Section: Discussionmentioning
confidence: 79%
“…The results of our ROC analyses suggest that the right hippocampal volume is a potential marker for differentiation between SZ and BD. To this end, multimodal functional neuroimaging studies [26,[51][52][53][54][55][56][57][58][59][60][61] that combine structural MRI [3,16,[18][19][20][21]23,[26][27][28][42][43][44]51,[61][62][63], functional MRI [26,[53][54][55][56][57][58][59][60][61]64,65], magnetic resonance spectroscopy [66][67][68][69], positron emission tomography [69][70][71][72], elec...…”
Section: Discussionmentioning
confidence: 99%
“…The results of our ROC analyses suggest that the right hippocampal volume is a potential marker for differentiation between SZ and BD. To this end, multimodal functional neuroimaging studies [ 26 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ] that combine structural MRI [ 3 , 16 , 18 , 19 , 20 , 21 , 23 , 26 , 27 , 28 , 42 , 43 , 44 , 51 , 61 , 62 , 63 ], functional MRI [ 26 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 64 , 65 ], magnetic resonance spectroscopy [ 66 , 67 , 68 , 69 ], positron emission tomography [ 69 , 70 , 71 , 72 ], electroencephalography, and magnetoencephalography [ 4 , 5 , 6 , 7 , 8 , 9 , 59 , ...…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found evidence of that lowered connectivity at baseline is either normalised or partly normalised after antipsychotic treatment 11,18 (although see also 50,51 ).…”
Section: Connectivity Changes In Antipsychotic-treated Patientsmentioning
confidence: 99%